Nanoparticles of gadolinium-incorporated Prussian blue with PEG coating as an effective oral MRI contrast agent for gastrointestinal tract imaging. Issue 6 (18th February 2016) - Perera, Vindya S.; Chen, Guojun; Cai, Qing; Huang, Songping D.
Abstract : Nanoparticles of gadolinium-incorporated Prussian blue show potential as a cellular T 1 -weighted oral MRI probe for imaging the gastrointestinal tract. Abstract : Biocompatible nanoparticles of gadolinium-incorporated Prussian blue with the empirical formula K0.94 Gd0.02 Fe[Fe(CN)6 ] exhibit extremely high stability against the release of Gd 3+ and CN − ions under the acidic conditions similar to stomach juice. The high r 1 relaxivity, low cytotoxicity and the ability of such nanoparticles to penetrate the cell membrane suggest that this coordination-polymer structural platform offers a unique opportunity for developing the next generation of T 1 -weighted oral cellular MRI probes for the early detection of tumors in the gastrointestinal tract.